ASPEK HUKUM FATWA MAJELIS PERMUSYAWARATAN ULAMA (MPU) TENTANG ALIRAN SESAT - Kurniawan Kurniawan (Faculty of Law, Universitas Jenderal Soedirman, 2014)
This study is aimed at describing constitutional and legal basis of MPU in Aceh, describing the history of existence of the Ulama’s roles in Aceh and also analyzing legal aspect and legal implication of deciding MPU Aceh concerning cult. The approaches used on this study are statute approach, cases approach, and historical approach. The result of analysis shows that fatwa issued by MPU Aceh concerning cult to several chairpersons of Islamic school (Pasantren/Dayah) in Aceh is against the law, especially Article 5 (b) Qanun Aceh No. 2 of 2009 on Aceh’s Ulama Consultative Assembly. Keywords: fatwa, Aceh’s Ulama Consultative Assembly, cult